Circe, i sofismi e le magie verbali. Nota a Plauto, Epidicus 604 - Cristiana Franco (Annali Online dell'Università di Ferrara. Sezione Lettere)
In Epidicus 604 Periphanes insults Acropolistis, a dolosa fidicina who pretended to be his daughter, addressing her as a Circam, Solis filiam. According to Rigaltius, the main point of the insult lies in Solis filia, an expression that he interprets as meaning “daughter of unknown father”. Other scholars wonder whether the abuse alludes to Acropolostis’ ‘metamorphic’ powers; others hold that it stands, more generally, for “tricky courtesan”. However, in the scene that precedes the passage, Acropolistis’ ‘magic’ consists in a display of sophistic ‘fake logic’ and acrobatic rhetoric, for which Circe was likewise notorious in ancient times, as the entries παιπαλώδης and Κίρκη in Suida and Etymologicum Magnum clearly testify.